2022
DOI: 10.1002/ajmg.a.62625
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization among youth with Ehlers–Danlos syndrome hypermobile type

Abstract: Ehlers-Danlos syndrome (EDS) is a heterogeneous group of inherited disorders of connective tissue. EDS hypermobility type (EDS-HT), characterized by joint hypermobility, is most common and increasingly recognized in pediatrics. Treatment involves protecting joints, preventing injuries, and managing symptoms/ comorbidities. Pediatric EDS-HT patients often see multiple medical providers; however, data on healthcare utilization (HCU) in this population are lacking. This retrospective, electronic chart review exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This likely represents more parental focus on evaluation and diagnosis of EDS in minors as there were more minors undergoing evaluation for EDS and HSD in this study. A previous study showed that health care utilization for those with EDS/HSD shifted from more diagnostic needs to more management of disease over time, however, the utilization of care remained high (Williams et al, 2022). Additionally, the more commonly utilized subspecialty T A B L E 3 Specialty care visits for respondents and minors with EDS care may represent a place to implement education about EDS/HSD to improve care and outcomes, but also may be ideal specialties to target for multidisciplinary care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This likely represents more parental focus on evaluation and diagnosis of EDS in minors as there were more minors undergoing evaluation for EDS and HSD in this study. A previous study showed that health care utilization for those with EDS/HSD shifted from more diagnostic needs to more management of disease over time, however, the utilization of care remained high (Williams et al, 2022). Additionally, the more commonly utilized subspecialty T A B L E 3 Specialty care visits for respondents and minors with EDS care may represent a place to implement education about EDS/HSD to improve care and outcomes, but also may be ideal specialties to target for multidisciplinary care.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of whether the diagnosis is hEDS or HSD, the standard treatment involves education and preventative care for symptoms that arise and involves many of the same medical subspecialties (Engelbert et al, 2017). Due to the varied clinical phenotypes in EDS, those with EDS demonstrated increased health care utilization (Williams et al, 2022). To address the many comorbidities and high disease burden in those with EDS, multidisciplinary care has been proposed to help facilitate coordination of care, maximize treatment, and reduce medical visits (Kalisch et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As hEDS continues to be classified as a rare disorder (and, therefore, is relatively less researched), and that the prevalent symptom is chronic pain, similarities and research may be drawn from the general chronic pain population in order to provide a theoretical background or basis for continued research within hEDS. Differences between hEDS and primary chronic pain disorders include potentially distinct underlying causes of pain in hEDS (structural abnormality in the form of joint hypermobility), additional co-morbid symptoms affecting multiple body systems and uniquely complex journeys within the healthcare system [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complex needs and multisystem involvement, children and adolescents with EDS often seek care from multiple health-care providers. 4 , 5 Multidisciplinary care is recommended for the treatment of EDS to improve coordination of care, reduce medical visits, and improve outcomes. 6 However, the development of a multidisciplinary care team is predicated on identifying the healthcare needs expressed by patients to inform which specialties are needed for inclusion in these clinics.…”
Section: Introductionmentioning
confidence: 99%